Diversity of Aerobic Bacteria Isolated from Oral and Cloacal Cavities from Free-Living Snakes Species in Costa Rica Rainforest - Artavia León, Allan (2017)
Costa Rica has a significant number of snakebites per year and bacterial infections are often complications in these animal bites. Hereby, this study aims to identify, characterize, and report the diversity of the bacterial community in the oral and cloacal cavities of venomous and nonvenomous snakes found in wildlife in Costa Rica.The snakes where captured by casual encounter search between August and November of 2014 in the Quebrada Gonzalez sector, in Braulio Carrillo National Park. A total of 120 swabs, oral and ´ cloacal, were taken from 16 individuals of the Viperidae and Colubridae families. Samples were cultured on four different media at room temperature. Once isolated in pure culture, colonies were identified with the VITEK 2C platform (bioMerieux). In order to ´ test the identification provided on environmental isolates, molecular analyses were conducted on 27 isolates of different bacterial species. Specific 16S rDNA PCR-mediated amplification for bacterial taxonomy was performed, then sequenced, and compared with sequences of Ribosomal Database Project (RDP). From 90 bacterial isolates, 40 different bacterial species were identified from both oral and cloacal swabs. These results indicate the diversity of opportunistic pathogens present and their potential to generate infections and zoonosis in humans.